2017
DOI: 10.3389/fmicb.2017.01258
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Emerging Human Mastitis Pathogens by MALDI-TOF and Assessment of Their Antibiotic Resistance Patterns

Abstract: Lactational mastitis constitutes one of the main causes of undesired weaning, depriving the mother–infant pair from the benefits of breastfeeding; therefore, this condition should be considered a relevant public health issue. The role of specific microorganisms remains unclear since human milk cultures and antibiotic susceptibility testing (AST) are not routinely performed, despite the fact that this would be key to ensure an early and effective diagnosis and treatment. The objective of this study was to descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 70 publications
3
47
0
Order By: Relevance
“…The MALDI-TOF technique is also gaining ground for bacteria of veterinary importance, originating from bovine, ovine, porcine, and avian sources and, to a lesser extent, of canine, caprine, and equine provenance (Randall et al, 2015). Several researchers have applied the technique to bacterial groups causing bovine mastitis, such as group B streptococci (Barreiro et al, 2010), group D streptococci (Werner et al, 2012), non-aureus staphylococci (Barreiro et al, 2010;Cameron et al, 2017;Mahmmod et al, 2018), Enterobacteriaceae (Rodrigues et al, 2017;Savage et al, 2017), and even lactational mastitis in humans (Marín et al, 2017). Classical phenotypical and biochemical tests have limitations-they typically take from one to several days to perform and read, and misidentification of bacteria is not uncommon (Bes et al, 2000;Taponen et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The MALDI-TOF technique is also gaining ground for bacteria of veterinary importance, originating from bovine, ovine, porcine, and avian sources and, to a lesser extent, of canine, caprine, and equine provenance (Randall et al, 2015). Several researchers have applied the technique to bacterial groups causing bovine mastitis, such as group B streptococci (Barreiro et al, 2010), group D streptococci (Werner et al, 2012), non-aureus staphylococci (Barreiro et al, 2010;Cameron et al, 2017;Mahmmod et al, 2018), Enterobacteriaceae (Rodrigues et al, 2017;Savage et al, 2017), and even lactational mastitis in humans (Marín et al, 2017). Classical phenotypical and biochemical tests have limitations-they typically take from one to several days to perform and read, and misidentification of bacteria is not uncommon (Bes et al, 2000;Taponen et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Mastitis can be classified as either noninfectious or infectious. Infectious mastitis is caused by bacterial invasion through the teat cistern or a fissure in the nipple , and Staphylococcus and Streptococcus are common mastitis pathogens in both humans and cows , suggesting that infectious mastitis shares some biological similarities among mammalian species.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, very few well-powered studies have so far focused explicitly on the impact of routine antibiotic usage for lactational breast abscess. 20 Previous studies have showed that Staphylococcus aureus, a frequent causative pathogen, is diversely resistant to antibiotics, 26,27 while in clinical practice, antibiotics are empirically administrated in many cases without definite etiology of infection, or even without the report of antibiotic sensitivity test. 26,27 This might worsen the condition of drug resistance and repeated courses might even increase the risk for opportunistic infection, such as Candida.…”
Section: Introductionmentioning
confidence: 99%
“…20 Previous studies have showed that Staphylococcus aureus, a frequent causative pathogen, is diversely resistant to antibiotics, 26,27 while in clinical practice, antibiotics are empirically administrated in many cases without definite etiology of infection, or even without the report of antibiotic sensitivity test. 26,27 This might worsen the condition of drug resistance and repeated courses might even increase the risk for opportunistic infection, such as Candida. [28][29][30] On account of inherent limitations of the studies available in the literature, well-designed studies on a larger scale are thus warranted to properly assess the role of antibiotics for the treatment of breast abscess in breastfeeding women.…”
Section: Introductionmentioning
confidence: 99%